Pengembangan Media Pembelajaran Berbasis Power Point Interaktif Pada Materi Sistem Pencernaan Manusia Kelas XI - Halawa, Tektonius; Nazara, Agustiaman; Lase, Natalia Kristiani (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of this study is to develop Power Point -based interactive learning media on digestive system material that is valid, practical, and effective. This research is development research using the Research and Development (R&D) development model. This research was carried out in class XI. The instrument used is a validation questionnaire which includes aspects of content feasibility (material), language feasibility, and design feasibility (media), student response questionnaires and learning outcomes. The data analysis in this study was carried out descriptively on all the data obtained. The results of the analysis show that the learning media is also very practical to be used by students. Based on the results of the study, it can be concluded that the media developed is suitable for use in the learning process of the digestive system